IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH (STUDI DI SMP MUHAMMADIYAH 2 SENTOLO): Bahasa Indonesia - Teng, Yan; Hidayati, Dian; Sukirman, Sukirman (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
In the context of international school-based management reform, in order to mobilize the momentum of change and lead innovation, the Principal of SMP Muhammadiyah 2 Sentolo initiated and actively led school-based management reform based on the subjective development needs of teachers and students. SMP Muhammadiyah 2 Sentolo attaches great importance to its own characteristics and needs, and achieves independent development under the premise of decentralization. Relevant personnel make joint decisions and participate in management. Although the management of educators and education personnel is good, finances are good, SMP Muhammadiyah 2 Sentolo has shortcomings in curriculum management and student management, but it has actively built a new learning school through its own management reform. This study analyzes the experience of SMP Muhammadiyah 2 Sentolo as an example of quality school-based management reform that can motivate, mobilize and help underprivileged students. The achievement of harmonious and balanced educational development is the goal of this study. This study mainly uses the case study method, by making SMP Muhammadiyah 2 Sentolo a special object to investigate and analyze educational phenomena in school-based management reform. The research was conducted using formal and informal individual interviews, as well as the collection of relevant documents and results.